Development of Interactive Teaching Materials Based on Local Wisdom of Bojonegoro in Indonesian Language Subject for Grade IV at MI Bahrul Ulum Balen - Durrotun Nafisah; Jauharoti Alfin (University of Muhammadiyah Malang, 2026)
Background: in the real context of MI Bahrul Ulum Balen Bojonegoro, the availability of interactive teaching materials that incorporate Bojonegoro local wisdom is still very limited. Most Grade IV Indonesian language materials are still in the form of general printed textbooks without enrichment of local cultural contexts such as folklore, local traditions, or the distinctive language of the Bojonegoro area. This condition potentially causes students to experience difficulties in relating lessons to their local cultural experiences and results in low motivation to learn Indonesian contextually. Objectives: Accordingly, the purpose of this study is to develop and implement interactive teaching materials based on Bojonegoro local wisdom to improve students’ understanding and engagement in Indonesian language learning for Grade IV at MI Bahrul Ulum Balen Bojonegoro. Methods: The method used in this study is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This study involved 20 students at the Elementary School level. The instruments used were a validation questionnaire by media experts and material experts, student response questionnaires, and learning outcome tests. Results: Validation by three experts indicated the module was feasible (average score 81.57%), and trial results showed significant improvement in student learning outcomes, with pre-test and post-test averages of 59% and 87%, respectively. Student response questionnaires indicated a 95.3% positive approval rate. Conclusions: The findings suggest that integrating local wisdom into interactive teaching materials enhances student engagement, comprehension, and contextual understanding while providing teachers with effective instructional support. The module is thus a valid, practical, and effective tool for improving Indonesian language learning in primary education.